Associations of developmental imbalance between sensation seeking and premeditation in adolescence and heavy episodic drinking in emerging adulthood. (15th May 2021) - McCabe, Connor J.; Wall, Tamara L.; Gonzalez, Marybel R.; Meruelo, Alejandro D.; Eberson‐Shumate, Sonja C.; Clark, Duncan B.; Nooner, Kate B.; Brown, Sandra Ann; Tapert, Susan F.
Abstract: Background: Dual systems theories suggest that greater imbalance between higher reward sensitivity and lower cognitive control across adolescence conveys risk for behaviors such as heavy episodic drinking (HED). Prior research demonstrated that psychological analogues of these systems, sensation seeking and premeditation, change from childhood through emerging adulthood, and each has been independently linked with HED. However, few studies have assessed whether change over time in these developing analogues is prospectively associated with HED. Moreover, we know of no research that has shown whether within‐person differences between higher sensation seeking and relatively lower premeditation across the adolescent period predict HED in emerging adulthood. Methods: Prospective data from the National Consortium on Alcohol and NeuroDevelopment in Adolescence study ( n = 715) were used to examine the association of sensation seeking and premeditation with HED among adolescents ages 16 to 20 years. We used novel applications of latent difference score modeling and growth curve analysis to test whether increasing sensation seeking, premeditation, and their imbalance over time are associated with HED across the study period, and whether these associations differed by sex. Results: Whereas premeditation increased linearly from adolescence through emerging adulthood across sexes, males reported growth and females reported decline in sensation seeking. Sensation seeking in adolescence (and not premeditation) was associated with higher levels of HED by emerging adulthood. Importantly, greater imbalance between sensation seeking and premeditation was associated with higher levels of HED by emerging adulthood though we note that variability capturing this imbalance correlated highly ( r = 0.86) with baseline levels of sensation seeking. Conclusions: Developmental imbalance between higher sensation seeking and lower premeditation in late adolescence may be a risk factor for greater HED in emerging adulthood. Abstract : Teens with high sensation seeking impulses and relatively low cognitive control may be at elevated risk for heavy episodic drinking (HED) through emerging adulthood. However, no studies had tested whether this developmental imbalance (DI) between these traits predicted such drinking behaviors. Using a novel analytic approach, this manuscript provided evidence that teens who had higher sensation seeking impulses relative to their cognitive control had more heavy drinking episodes by emerging adulthood, which provided evidence of this developmental imbalance theory.